Innovation under an umbrella: how can blockchain contribute to corporate innovation in the age of globalization - Zhang, Runze; Chen, Xi; Li, Zhijun; Qiu, Peiyang (Technological and Economic Development of Economy, 2023)
In the age of globalization, enterprises have faced new challenges and opportunities for innovative behavior. Increasing cultural exchanges provide enterprises with a wealth of information and knowledge, but also exacerbate the risk of information loss. Therefore, information security has become an increasingly critical issue. Blockchain technology is an effective guarantee for the success of enterprise innovation in such circumstances. Enterprises can access information across national boundaries and avoid the risk of a cultural clash or a leak of information due to the security and traceability of blockchain technology. In the era of globalization, blockchain technology has become an umbrella for enterprises to exploit cultural diversity. This study presents a DDD model that illustrates how blockchain firms can benefit from cultural diversity to produce innovative products. Specifically, firms that utilize blockchain increase their innovation output by 36.17% compared to those that do not. Additionally, it explores how firms can benefit from the spillover of external knowledge and how traditional models of R&D through equipment purchases give way to new models of bringing in talent for knowledge exchange using blockchain. The model presented in this study provides a novel theoretical perspective on how emerging technologies affect corporate innovation, emphasizing the importance of blockchain technology to corporate innovation in an era of globalization with increasing cultural exchanges. It also provides a new perspective on the application of emerging technologies.